Finite-time H∞ control for a class of discrete-time switched singular time-delay systems subject to actuator saturation - Ma, Yuechao; Fu, Lei; Jing, Yanhui; Zhang, Qingling (Applied mathematics and computation, 2015)
This paper concerns with the finite-time H∞ control problem for a class of discrete-time switched singular time-delay with actuator saturation. Not only linear matrix inequality conditions for the systems but also average dwell-time of switching signal is given to guarantee regular, causal and finite-time boundedness for the discrete-time switched singular time-delay system. Moreover, sufficient conditions are presented to ensure the H∞ disturbance attenuation level, and the design method of H∞ controller is developed by solving linear matrix inequalities (LMI) optimization problem without any decompositions of system matrices and equivalent transformation. Furthermore, the function in the proof procedure belongs to multiple Lyapunov-like functions whose advantage lies in their flexibility. Finally, numerical examples are employed to verify the effectiveness of the proposed methods and to illustrate the significant improvement on the conservativeness of some reported results in the literature.